Spatio-temporal distribution modeling of dolphinfish (Coryphaena hippurus) in the Pacific Ocean off Peru using artisanal longline fishery data. (November 2019) - Torrejón-Magallanes, Josymar; Grados, Daniel; Lau-Medrano, Wencheng
Abstract: To better understand and characterize the distribution of the dolphinfish Coryphaena hippurus in the Pacific Ocean off Peru, we analyzed spatio-temporal catch per unit effort (CPUE) data from the artisanal longline dolphinfish fishery and oceanographic variables measured from October–March during 2010–2017. A Delta-GAM approach determined that high dolphinfish CPUE occurred during the period from November–January between 9-11°S at an average of 190 nautical miles (nm) from the coast. From February–March, the highest CPUE was located along the coast up to 115 nm offshore between 12-13°S, which suggested that dolphinfish migrate to the southeast during austral summer. However, there was no evidence of a reverse migration towards the northwest, although this result must be corroborated with data taken outside of the dolphinfish fishing season (October–April) in future studies. According to the environmental variables, dolphinfish preferred to stay in waters with sea surface temperatures (SST) that ranged from 22-24 °C, low chlorophyll-a concentrations (CHL; < 1 mg m −3 ), and surface sea heights (SSH) that ranged from 0.10-0.20 m. The information derived from this study, such as the maps, spatial indicators, and time series, contribute to the knowledge of how the spatial distribution of the dolphinfish and dolphinfish CPUE may vary under future climate conditions and provide some clues that will facilitate fishing ground forecasts in both the short and long term. Finally, our results may provide tools to develop or improve the conservation and management strategies of this species, which supports one of the most important artisanal fisheries in Peru.